PROFITABILITY OF SHEEP FINISHED ON MIXED SWARD DIETS IN KAJIADO COUNTY, KENYA - Benson Mulei; Kuria, Simon; Manyeki, John; Maweu, Annastacia (Socio-Economics/Agribusiness Department, 2024)
Availability of economical and easily accessible feeds that are high in both quantity and quality is a crucial factor in sustainable livestock production. The study aimed at determining the profitability of finishing sheep by supplementing using protein rich leguminous feeds. In a completely randomized experimental design, a group of 18 mass selected dorper yearling sheep, aged 17-19 months and an average body weight of 20.5±2.9 Kgs were assigned into 6 diet experimental units of 3 animals each. Analysis of variance and economic analyses showed Bush rye+Desmodium and African fox tail+Lucerne diets as the leading with net weight gain of 3.0±0.7 Kgs and 2.8±0.5 Kgs and profitable returns of Ksh 65,979.00 and Ksh 30,906.00 respectively for 100 units’ sheep establishment at the market live body weight price of Ksh 400/kg. Selection of a cost effective legume and right breed and genetics of the animal was an essential consideration for enhanced enterprise profitability.